ChemInform Abstract: (Cs6Cl)6Cs3 [Ga53Se96]: A Unique Long Period‐Stacking Structure of Layers Made from Ga2Se6 Dimers via cis or trans Intralayer Linking. Issue 16 (March 2016) - Lin, Hua; Chen, Hong; Lin, Zi‐Xiong; Zhao, Hua‐Jun; Liu, Peng‐Fei; Yu, Ju‐Song; Chen, Ling
Abstract: The new title compound is synthesized by reaction of Ga and Se in a CsCl flux in the presence of Mn (CsCl:Mn:Ga:Se = 6:4:5:12, 1273 K, 4 d; 60% yield).